A Study on PAYTM Usage and Problems Faced among the Employees of XYZ Company Ltd. - Dr. A. Sandhya Rani (International Journal of Engineering and Management Research, 2018)
In today’s-world, Smartphone has become an important part of everyday life. As it has become more affordable, the number of Smartphone users has increased dramatically. Smart phones are able to run a variety of software components, known as “apps”. PayTM, the mobile wallet and e-commerce start-up, became a household name in the last few months. So much so that it has become a generic term associated with any e-wallet and has become an all-pervasive brand with high recall value. Demonetisation gave a fillip to mobile wallet firms like PayTM helping them gain users at exponential rates every day.. The main objective is to study PayTM usage and problems faced by the employees of XYZ company Ltd. Study is analyzed considering 15 alternatives with a sample size of 150. Chi square analysis is done to examine if there is a significant influence of AGE on the usage of the Mobile wallet (PayTM). Study has proved it is.